2018
DOI: 10.1159/000489165
|View full text |Cite
|
Sign up to set email alerts
|

H2 Receptor Antagonists versus Proton Pump Inhibitors in Patients on Dual Antiplatelet Therapy for Coronary Artery Disease: A Systematic Review

Abstract: Objectives: Mitigating the gastrointestinal (GI) bleeding risks of dual antiplatelet therapy (DAPT) is a common clinical concern. While proton pump inhibitors (PPIs) remain the most effective therapy, their adverse events warrant considering alternatives, including Histamine 2 receptor antagonists (H2RAs). Methods: We searched for randomized controlled trials in MEDLINE, EMBASE, PubMed, and Cochrane Central Register of Controlled Trials, published from 1980 to 2016. After screening, 10 trials were eligible. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
0
17
0
Order By: Relevance
“…Data comparing the efficacy of PPIs and H2RAs for CIGIB prophylaxis in CCU patients are limited. A systemic review of RCTs indicated that PPIs were superior to H2RAs for gastrointestinal protection in patients on DAPT; however, the end‐points of the studies were not CIGIB 30 . Our sensitivity analyses failed to detect any plausible scenario in which PPIs were superior to H2RAs or the control for the prevention of CIGIB in CCU patients, and we did not find significant differences in the efficacy of different acid suppressant types or drug administration routes for GIB prophylaxis among the three groups; this supports the result that prophylactic PPI use does not reduce the incidence of GIB in patients receiving DAPT 13…”
Section: Discussionmentioning
confidence: 99%
“…Data comparing the efficacy of PPIs and H2RAs for CIGIB prophylaxis in CCU patients are limited. A systemic review of RCTs indicated that PPIs were superior to H2RAs for gastrointestinal protection in patients on DAPT; however, the end‐points of the studies were not CIGIB 30 . Our sensitivity analyses failed to detect any plausible scenario in which PPIs were superior to H2RAs or the control for the prevention of CIGIB in CCU patients, and we did not find significant differences in the efficacy of different acid suppressant types or drug administration routes for GIB prophylaxis among the three groups; this supports the result that prophylactic PPI use does not reduce the incidence of GIB in patients receiving DAPT 13…”
Section: Discussionmentioning
confidence: 99%
“…However, in a large analysis of administrative claims from commercial and Medicare Supplemental plans from 2001 to 2014 in the United States, it was found no evidence that prescription of PPIs increased the risk of MI compared with prescription H 2 RA [57]. In patients taking antiplatelet agents, both as monotherapy and DAT, PPIs were superior to H 2 RA in preventing GI bleeding [58]. However, an increased risk (OR 1.40, 95% CI: 1.10-1.77) of recurrent MI was reported in 2009 in patients taking clopidogrel and PPIs [59].…”
Section: Pharmacological and Clinical Interactions Between Proton Pummentioning
confidence: 99%
“…They are a group of drugs commonly used as a standard therapy in gastroesophageal reflux disease (GERD) and acidity disorders of the upper gastrointestinal tract. Due to their proven effectiveness in suppression of acid secretion by gastric parietal cells [1], PPI are used both in the treatment and the prevention of gastric and duodenal ulcers, gastroesophageal reflux disease and in the eradication of Helicobacter pylori. Their ubiquitous use is also due to the administration of PPI to patients receiving non-steroidal anti-inflammatory drugs or antiplatelet agents [2,3].…”
Section: Introductionmentioning
confidence: 99%